2021
DOI: 10.3389/fnagi.2021.678359
|View full text |Cite
|
Sign up to set email alerts
|

Regional Spontaneous Neural Activity Alterations in Type 2 Diabetes Mellitus: A Meta-Analysis of Resting-State Functional MRI Studies

Abstract: Objective: Resting-state functional magnetic resonance imaging (rs-fMRI) studies have revealed inconsistent regional spontaneous neural activity alterations in patients with type 2 diabetes mellitus (T2DM). The aim of our meta-analysis was to identify concordant regional spontaneous neural activity abnormalities in patients with T2DM.Methods: A systematic search was conducted to identify voxel-based rs-fMRI studies comparing T2DM patients with healthy controls. The permutation of subject images seed-based d ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…In addition, we observed decreased spontaneous brain activity in the right superior temporal gyrus, which was an important brain alternation for patients with depression ( 136 ). Consistent with our research, some meta-analyses showed that the gray matter volume (GMV) and neural activity of the superior temporal gyrus decreased significantly in T2DM patients, which may be related to emotional disorders ( 33 , 137 , 138 ). In future, the effects of depression on the brain structure and function of patients with diabetes should be consider independently.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we observed decreased spontaneous brain activity in the right superior temporal gyrus, which was an important brain alternation for patients with depression ( 136 ). Consistent with our research, some meta-analyses showed that the gray matter volume (GMV) and neural activity of the superior temporal gyrus decreased significantly in T2DM patients, which may be related to emotional disorders ( 33 , 137 , 138 ). In future, the effects of depression on the brain structure and function of patients with diabetes should be consider independently.…”
Section: Discussionsupporting
confidence: 90%
“…In the last few years, many studies have proposed that abnormal neural spontaneous activity might be the internal mechanism for cognitive impairment in T2DM subjects based on results obtained using the amplitude of low-frequency fluctuation (ALFF) method ( Liu et al, 2021 ). Compared to healthy controls (HCs), T2DM subjects have lower ALFF in some regions, such as the frontal lobe, inferior parietal lobule, precuneus, posterior cingulate gyrus, and posterior cerebellar lobe ( Wang et al, 2011 ; Xia et al, 2013 ; Cui et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The right superior temporal gyrus is mainly responsible for processing objects and spatial information (50). A meta-analysis confirmed that the right superior temporal gyri had restingstate function alterations in T2DM relative to healthy people (51). VBM analysis found that gray matter volume in patients with T2DM was decreased in the right superior temporal gyrus (52).…”
Section: Discussionmentioning
confidence: 88%